2013
DOI: 10.1177/0731684413509424
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength of sandwich core materials subjected to loading rates relevant to water slamming

Abstract: Sandwich composite materials are widely used within the marine industry, particularly as hull panels. Water impact loads, known as slamming, can be very significant for these structures, particularly for high-speed craft. The transient nature of slamming loads means that the loads are applied very quickly, which can cause stress and strain rates that are high enough to affect the resulting strength of the core material, particularly for polymeric foams. The aim of this paper is to characterise the shear streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…For these tests, the resulting strength values are only to be used if they are lower than the static strength values; if they are higher, the static strength values must be used. Battley et al [27] have used a similar approach to the DNV-HSLC dynamic beam test. Two testing approaches were used, a custom servo-hydraulic beam testing system and a drop weight impact-testing machine.…”
Section: Strength Characterisation Of Core Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these tests, the resulting strength values are only to be used if they are lower than the static strength values; if they are higher, the static strength values must be used. Battley et al [27] have used a similar approach to the DNV-HSLC dynamic beam test. Two testing approaches were used, a custom servo-hydraulic beam testing system and a drop weight impact-testing machine.…”
Section: Strength Characterisation Of Core Materialsmentioning
confidence: 99%
“…In the case of beams, these can also be done at higher loading rates. This is important for slamming applications as the transient nature of slamming loads means that the loads are applied very quickly (typically in the order of milliseconds), which can cause stress rates that are high enough to affect the resulting strength of the core material, particularly for polymeric foams [27].…”
Section: Strength Characterisation Of Core Materialsmentioning
confidence: 99%
“…There is a significant space for further improving structural optimization and mechanical properties of composite materials. 16…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant space for further improving structural optimization and mechanical properties of composite materials. [1][2][3][4][5][6] A co-cured composite structure with double-layer damping membranes embedded (CCSDDME) is a new type of pre-processing damping structure that consists of a composite panel layer with damping material layers embedded into the composite. The composite structure with a damping layer created using a traditional process has disadvantages in that the interlayer bonding performance is poor, the damping material easily ages, and the damping layer thickness cannot be too thick.…”
Section: Introductionmentioning
confidence: 99%
“…Through experimental testing 11–17 and numerical modelling, 10 the mechanical properties of cellular solids are found to be primarily dependent on relative density (the ratio of the density of cellular solids to the density of base materials). However, it is often found that real foams have stiffness and strength much lower than those of idealized foams, such as Kelvin foam.…”
Section: Introductionmentioning
confidence: 99%